PEMBERIAN INTERVENSI RENDAM KAKI TERHADAP PENURUNAN TEKANAN DARAH PADA NY. M DI DESA ANJIR PASAR - Tries Mei Rivaldy; Tina Handayani Nasution (PENA NURSING, 2025)
Background: Hypertension sufferers continue to increase throughout the world. Hypertension that is not managed properly can cause death and disability. One treatment that can be done independently by sufferers is to soak their feet in warm water. Objective: To implement nursing care for Mrs. M through the main intervention of providing a foot soak to lower blood pressure. Method: This research used a descriptive case report design on a hypertensive patient in Paminggir Village. Data were collected using a medical-surgical nursing assessment sheet through interviews, observation and physical examination. The results of the study were carried out by planning and implementation of the foot soak until evaluation. Results and Discussion: The evaluation results showed that blood pressure decreased from 154/95 mmHg menjadi 140/90 mmHg after being given therapy for 3 days. Foot soak techniques can have a relaxing effect and widen the arteries so that blood pressure decreases. Conclusion: There was a decrease in blood pressure in Ms. M with a diagnosis of ineffective health management through foot soak intervention.